Application of Local Wheat Straw for Building Material and Products with Gypsum Binders (Journal of Architectural Design, 2023)
Dependencies describing the effect of crushed local wheat straw additives of different composition and specific surface area on the main physical-technical properties of construction gypsum have been defined. The effectiveness of adding crushed local wheat straw to construction gypsum increases with a decrease in the content of undrained clay from 14.1% to 9.5%. Gypsum-straw binder compositions have been developed, in which from 20 to 30% of construction gypsum is replaced by agricultural production waste, i.e., crushed wheat straw, without a significant decrease in physical and technical indicators